Protocol for the isotoxic intensity modulated radiotherapy (IMRT) in stage III non-small cell lung cancer (NSCLC): a feasibility study. Issue 4 (15th April 2016) - Haslett, Kate; Franks, Kevin; Hanna, Gerard G; Harden, Susan; Hatton, Matthew; Harrow, Stephen; McDonald, Fiona; Ashcroft, Linda; Falk, Sally; Groom, Nicki; Harris, Catherine; McCloskey, Paula; et al.
Abstract : Introduction: The majority of stage III patients with non-small cell lung cancer (NSCLC) are unsuitable for concurrent chemoradiotherapy, the non-surgical gold standard of care. As the alternative treatment options of sequential chemoradiotherapy and radiotherapy alone are associated with high local failure rates, various intensification strategies have been employed. There is evidence to suggest that altered fractionation using hyperfractionation, acceleration, dose escalation, and individualisation may be of benefit. The MAASTRO group have pioneered the concept of 'isotoxic' radiotherapy allowing for individualised dose escalation using hyperfractionated accelerated radiotherapy based on predefined normal tissue constraints. This study aims to evaluate whether delivering isotoxic radiotherapy using intensity modulated radiotherapy (IMRT) is achievable. Methods and analysis: Isotoxic IMRT is a multicentre feasibility study. From June 2014, a total of 35 patients from 7 UK centres, with a proven histological or cytological diagnosis of inoperable NSCLC, unsuitable for concurrent chemoradiotherapy will be recruited. A minimum of 2 cycles of induction chemotherapy is mandated before starting isotoxic radiotherapy. The dose of radiation will be increased until one or more of the organs at risk tolerance or the maximum dose of 79.2 Gy is reached. The primary end point is feasibility, with accrual rates, local control and overall survival our secondary end points. Patients will be followed up for 5 years. Ethics and dissemination: The study has received ethical approval (REC reference: 13/NW/0480) from the National Research Ethics Service (NRES) Committee North West—Greater Manchester South. The trial is conducted in accordance with the Declaration of Helsinki and Good Clinical Practice (GCP). The trial results will be published in a peer-reviewed journal and presented internationally. Trial registration number: NCT01836692; Pre-results.